Hepatitis B and hepatocellular carcinoma recurrence after living donor liver transplantation: The role of the Milan criteria - Sezgin Vatansever,; Rasim Farajov,; Hüseyin Cahit Yılmaz,; Murat Zeytunlu,; Zehra Betül Paköz,; Murat Kılıç, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The aim of this study was to evaluate the effect of the Milan criteria on the hepatitis B virus (HBV) and hepatocellular carcinoma (HCC) recurrence in patients who underwent living donor liver transplantation due to HBV-induced cirrhosis and HCC. Materials and Methods: We evaluated a total of 142 patients, 88 who underwent transplantation due to HBV-induced cirrhosis and 54 due to HCC, between 2009 and 2014. In the posttranplant period, after the HBsAg seroconversion, 400 IU of hepatitis B immunoglobulin were applied intramuscularly every 2 weeks, and daily nucleos(t)ide analogs were continued as prophylaxis. The HBV recurrence was defined as the presence of HBsAg in serum. Patients were screened for alpha-fetoprotein levels and imaging for evaluation of HCC recurrence. Results: The average follow-up period was 26 (2-65) months. Fifty-four patients had HCC. The HCC recurrence was observed in 12 patients during the follow-up period. The HBV recurrence was observed in four patients. Three of the patients who developed HBV recurrence had liver transplantation due to HCC. Tumor recurrence was observed 1.4-12 months following the HBV recurrence. The HCC recurrence within the Milan criteria and beyond the Milan criteria was 0% vs. 28.4 % in the first year and 3.4% vs. 47.5% in the third year. The cumulative incidence of the HBV recurrence was 2.8% and 3.7% for the first year and 3.7% for the third year. The HBV recurrence was more frequently detected in patients with HCC (p=0.048), especially with HCC beyond the Milan criteria (p=0.044). Conclusion: The HBV recurrence should be evaluated as a predictor of the HCC recurrence in patients who underwent liver transplantation due to HCC with exceeding Milan criteria. Cite this article as: Vatansever S, Farajov R, Yılmaz HC, Zeytunlu M, Paköz ZB, Kılıç M. Hepatitis B and hepatocellular carcinoma recurrence after living donor liver transplantation: The role of the Milan Criteria. Turk J Gastroenterol 2019; 30: 75-80.